Students’ evaluation of health promotion learning outcomes:a case from a Malaysian institute - Daher, Aqil M.; Osman, Muhamed T.; Selamat, Mohd Ikhsan; Noor, Aini M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Health promotion (HP) is getting recognition in most medical school curricula. The aim of this study is to assess students’ perception of learning outcomes and the main factors affecting these outcomes. Methods:This was a prospective cross-sectional which involved all year four medical students who completed the population health posting for two successive academic sessions 2011-2012 and 2012-2013. Self-administered questionnaire was used to assess course characteristics, teaching environment and acquired knowledge, skills and attitude. Response to each survey question was described. Structural Equation Modelling was used to test the relation between course characteristics, teaching environment and knowledge, skills and attitude. Path coefficients with corresponding significance test were presented. Results: Three hundred and thirty students with mean age of 22.6 years returned the completed questionnaire. There were about 69.1 % female students and 30.9 % males. Most respondents gave positive feedback regarding course characteristics. However, around 47% were not sure about clarity of the objectives. Students provided favourable responses to the statement evaluating lecturer performance and the class environment including opportunities for learning. Majority of respondents showed favourable response to statement assessing the defined attitude, skills and attitude. Lower higher ratings were observed for statements reflecting respondent autonomy, ability to work in difficult situation and managerial abilities. Path model showed that teaching environment impacted knowledge, skills and attitude, while course characteristic impacted the gained attitude only. Conclusions:Health promotion program is perceived to be sufficient to prepare students for professional life. Teaching environment had more impact on learning outcomes.